2021
DOI: 10.1002/star.202100114
|View full text |Cite
|
Sign up to set email alerts
|

Novel Malto‐Oligosaccharide‐Producing Amylase AmyAc from Archangium sp. Strain AC19 and Its Catalytic Properties

Abstract: Functional maltooligosaccharides (MOSs) derived from starch have potential applications in the food industry and medicine due to their specific functional properties. In this study, a novel maltose (G2) and maltotriose (G3)-producing amylase AmyAc from Archangium sp. strain AC19 is identified. AmyAc is a protein of 874 amino acids, with an N-terminal signal peptide as well as hydrolase family 13 (GH13) catalytic and C-terminal binding modules. However, its sequence is not highly similar to any of the reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In our previous studies, maltohexaose-forming α-amylase AmyM [ 7 ], α-amylase AmyC [ 32 ], maltogenic amylase CoMA [ 9 ] and G2 + G3-producing amylase AmyAc [ 33 ] have been identified from myxobacteria Corallococcus and Archangium . AmyCf from Cystobacter shares low sequence identity (<30%) with these enzymes except for AmyM (42%), and AmyCf is the first identified α-amylase from Cystobacter .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, maltohexaose-forming α-amylase AmyM [ 7 ], α-amylase AmyC [ 32 ], maltogenic amylase CoMA [ 9 ] and G2 + G3-producing amylase AmyAc [ 33 ] have been identified from myxobacteria Corallococcus and Archangium . AmyCf from Cystobacter shares low sequence identity (<30%) with these enzymes except for AmyM (42%), and AmyCf is the first identified α-amylase from Cystobacter .…”
Section: Resultsmentioning
confidence: 99%
“…Otherwise, no hydrolytic or glucanotransferase activity was observed from G4, G5 and G6 ( Figure 5 c), indicating the strict substrate selectivity of AmyCf. In our previous study, we identified that AmyAc from Archangium hydrolyzes G4 and G5 into G2 + G2 and G2 + G3, respectively, resulting the accumulation of G2 and G3 as the main products [ 33 ]. No action of AmyCf toward G5 and G6 indicates that AmyCf may bind starch chains with DP values more than 9, resulting in the production of G2, G3, and G4.…”
Section: Resultsmentioning
confidence: 99%
“…The amylase AmyAc from Archangium sp. Strain AC19 also has maximum hydrolytic activity on soluble starch, however, it has low hydrolytic activity on wheat starch and corn starch, its activity decreased by 67% and 84%, respectively, compared to that on soluble starch (22).…”
Section: Substrate Speci City Of Amyflamentioning
confidence: 96%